P150 THE HUMAN FC GAMMA RIIA H131 POLYMORPHISM IS A NEONATAL RECEPTOR (FCRN)-DEPENDENT HIGH RESPONDER VARIANT IN INFLAMMATORY BOWEL DISEASE. (7th February 2019) - Hubbard, Jonathan; Pyzik, Michal; Rath, Timo; Andersen, Jan Terje; Gandhi, Amit; Foss, Stian; Grevys, Algirdas; Glickman, Jonathan N; Fiebiger, Edda; Roopenian, Derry; Sandlie, Inger; Baker, Kristi; et al.
Abstract: Human FcγRIIa (CD32a) contains a prevalent and clinically relevant polymorphism, possessing either a histidine (H) (CD32a H )- or arginine (R) (CD32a R ) at amino acid position 131. Individuals expressing the CD32a H variant have higher risk of Crohn's disease and ulcerative colitis through unknown mechanisms. We show that CD32a H binds IgG immune complexes (IC) more actively than its counterpart, CD32a R, especially in acidic environments typical of intracellular endosomes that process IC in antigen presenting cells (APC) for antigen presentation and downstream activation of T cells. We further found that IC-induced APC functions associated with CD32a required the presence of an endosomal IgG receptor, the neonatal Fc receptor (FcRn). Under acidic conditions in which FcRn normally operates, FcRn was found to form a ternary complex with CD32a bridged by IC that determines APC function and T cell activation. Blockade of FcRn binding to IC in this ternary complex in APC with the anti-FcRn monoclonal antibody DVN24 significantly decreased APC stimulation of T cells in vitro . Importantly, compared to CD32a R -expressing APC, CD32a H -associated T cell activation by APC was more significantly inhibited by DVN24. Consistent with this, FcRn blockade by DVN24 more effectively ameliorated IgG-induced colitis in human transgenic mice expressing CD32a H compared to mice expressing CD32a R . These CD32a polymorphic variant-specific effects of FcRn blockade were further confirmed in an IgG-dependent mouse model of rheumatoid arthritis using CD32a H and CD32a R human transgenic mice. Thus, CD32a H more actively engages FcRn in a ternary complex with IgG IC compared to its allelic counterpart, CD32a R, and exhibits increased FcRn-dependence during IgG IC-induced disease. These studies carry important implications for the precision use of therapeutic antibodies based on CD32a haplotype and reveal a mechanism whereby CD32a H is the high-responder CD32a variant associated with Crohn's disease and ulcerative colitis. The CD32a H variant binds (A) IgG and (B) FcRn more strongly and is more susceptible to FcRn blockade (C) in vitro and (D, E) in an IgG-mediated colitis model in vivo .